The Effect of ÔÇ£Kids ModerationsÔÇØ Interactive Multimedia on Religious Moderation Attitudes in Early Childhood - Fahrun Nisak, Farahh; Munawaroh, Hidayatu; Abbas, Salbia (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
This research aims to determine the effect of interactive multimedia on religious moderation attitude in early childhood. The research used quasi-experimental method. One group pretest posttest was chosen as the design of the research. Data were collected by using checklist observation and analyzed using t-test. Results showed that religious moderation attitude in early childhood was increased by applying ÔÇ£Kids ModerationsÔÇØ interactive multimedia in learning process. Therefore, multimedia can be used as a tool to introduce religious moderation attitude since an early age and prevent intolerance as a root of radicalism in the future.